Rice heavy metal P-type ATPase OsHMA6 is likely a copper efflux protein - Wenli, Zou; Chang, Li; Yajun, Zhu; Jingguang, Chen; Haohua, He; Ye, Guoyou (Elsevier, 2020)
P1B-type heavy metal ATPases (HMAs) are transmembrane metal-transporting proteins that play a key role in metal homeostasis. We here reported the characterization of rice OsHMA6, a member of the P1B-type ATPase family. Phylogenetic tree analysis showed that OsHMA6 belonged to the Cu/Ag subgroup of the HMA family and had a close evolutionary relationship with OsHMA9. Amino acid sequence alignment showed 82.78% consistency between OsHMA6 and OsHMA9. OsHMA6 expressed in all organs at different growth stages, including spikelet, and abundant in leaf blades, however, OsHMA9 most strongly expressed in roots, but very low in spikelet. Excessive Cu2+ can up-regulate the expression of OsHMA6 and OsHMA9 in rice seedlings. The heterologous expression in yeast showed that OsHMA6 can significantly rescue the growth of yeast strain CM52 when supplied with 3 or 6 mmol/L Cu2+. Compared with the empty vector pYES2, the Cu concentration in OsHMA6-pYES2 decreased by 23.4% and 30.3% under 3 or 6 mmol/L Cu2+, respectively. Subcellular localization revealed that OsHMA6 was located in the plasma membrane. These results suggested that OsHMA6, similar to OsHMA9, is likely a copper efflux protein located in the plasma membrane.